Mathematical Modeling of Fresh Green Pepper (Capsicum L.) Dried at Different Powers in Microwave Oven - Fatma Coşkun Topuz (Turkish Journal of Agriculture: Food Science and Technology)
In this research, fresh green peppers were dried in a kitchen microwave oven at 600W, 700W and 800W. The drying curves of the study were compared with 5 different thin layer drying models in the literature. The changes in the moisture values of the samples against time were expressed graphically. R2, χ2 and RMSE values were used to determine the most suitable model for dried green peppers. Color values of fresh and dried peppers were determined. It was found that the L* and b* values of the dried peppers were lower, and the a* value was higher than the fresh green peppers. In addition, the rehydration rate of dried peppers was calculated. It was determined that the rehydration ability of the peppers decreased as the applied microwave power increased. For this reason, it was found that the peppers with the highest rehydration rate were those dried with 600W. Also, it was found that the most suitable model for all microwave powers among the five drying models was the Logarithmic drying model. It was calculated that the R2 values of the drying models ranged between 0.830-0.999, χ2 values between 0.0001- 0.4684 and RMSE values between 0.0014-0.6121. It was determined that the highest R2 (0.997-0.999), the lowest χ2 (0.0001-0.0002) values, and the lowest RMSE (0.0014-0.0035) values for all microwave powers belong to the Logarithmic drying model.